PENGARUH TINGKAT PENGANGGURAN TERBUKA, TINGKAT PENDIDIKAN, UPAH MINIMUM TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA TIMUR TAHUN 2017-2024 - Ralita Widyawati; Erwan Aristyanto (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2025)
This study aims to analyze the effect of open unemployment rate, education level, and minimum wage on economic growth in East Java Province during the period 2017-2024. The approach used is quantitative with an explanatory research design. The data were analyzed using panel data regression method that includes time dimension and geographical area, and supported by statistical tests to measure the significance of the influence of each variable. The results show that the open unemployment rate has a negative and significant effect on economic growth. In contrast, education level has a positive and significant effect on economic growth. Meanwhile, the minimum wage also has a significant but negative effect on economic growth, indicating that an increase in the minimum wage that is not proportional to productivity can hinder economic growth. Simultaneously, the three independent variables significantly affect economic growth in East Java Province. The R-squared value of 41.80% indicates that the variation in economic growth can be explained by these three variables, while the rest is influenced by other factors outside the model.